The colour variation in Vaccinium vitis-idaea berries from North Karelia - Chunaev, Aleksandr S.; Bondarenko, Ludmila V.; Barabanova, Larissa V. (2002)
The colour variation in red bilberry (Vaccinium vitis-idaea) berries from North Karelia has been studied applying digital photography.Plants with ripe berries differing in colour have been collected on the Malyj Gorelyj island in the White sea. The plants have been transferred to the laboratory,where digital photographs of plant samples and of detached berries have been taken by Agfa ePhoto 1680 camera.Image analysis confirms visually observed differences in colour of berries from different plants.Colour difference between normal antocian pigmented ''red'' berries and non-pigmented ''white'' ones significantly exceeds minimal colour difference,whereas ''rose'' berries possessing intermediate level of pigmentation could not always be clearly distinguished from non-pigmented berries.Our data proofs the applicability of digital photography to studies on colour variations in natural populations.